Discovery of Naturally Etched Fission Tracks and Alpha-Recoil Tracks in Submarine Glasses: Reevaluation of a Putative Biosignature for Earth and Mars - Jason E. French; David F. Blake (International Journal of Geophysics)
Over the last two decades, conspicuously “biogenic-looking” corrosion microtextures have been found to occur globally within volcanic glass of the in situ oceanic crust, ophiolites, and greenstone belts dating back to ~3.5 Ga. These so-called “tubular” and “granular” microtextures are widely interpreted to represent bona fide microbial trace fossils; however, possible nonbiological origins for these complex alteration microtextures have yet to be explored. Here, we reevaluate the origin of these enigmatic microtextures from a strictly nonbiological standpoint, using a case study on submarine glasses from the western North Atlantic Ocean (DSDP 418A). By combining petrographic and SEM observations of corrosion microtextures at the glass-palagonite interface, considerations of the tectonic setting, measurement of U and Th concentrations of fresh basaltic glass by ICP-MS, and theoretical modelling of the present-day distribution of radiation damage in basaltic glass caused by radioactive decay of U and Th, we reinterpret these enigmatic microtextures as the end product of the preferential corrosion/dissolution of radiation damage (alpha-recoil tracks and fission tracks) in the glass by seawater, possibly combined with pressure solution etch-tunnelling. Our findings have important implications for geomicrobiology, astrobiological exploration of Mars, and understanding of the long-term breakdown of nuclear waste glass.